Generalized stress–strain recovery formulation applied to functionally graded spherical shells and panels under static loading. (15th November 2016) - Viola, Erasmo; Rossetti, Luigi; Fantuzzi, Nicholas; Tornabene, Francesco
Abstract: The present investigation concludes the triad of papers by the first three authors concerning the 2D-unconstrained third order shear deformation theory for shell-like structures. Here, the static behavior of functionally graded spherical shells and panels subjected to uniform loadings at the extreme surfaces is studied. The material properties are graded in the thickness direction according to a four parameter power law. The structural model involves the a posteriori stress and strain recovery procedure. The obtained governing equations are solved by means of the GDQ numerical technique. An extensive numerical investigation is carried out to characterize the effect of material parameters on the stress, strain and displacement profiles along the thickness direction. The second order equilibrium operators, of the fundamental system of equations for functionally graded spherical shells and panels, are reported in the extended form.